Dynamic capabilities in small and medium manufacturing firms in rural Finland - role of social capital? - Petri Ruuskanen; Tomi Kankainen (European Regional Science Association (ERSA), 2011)
During the last decade, there has been wide agreement on the importance of dynamic capabilities on economic performance of firms. Simultaneously an increasing literature suggests that economic dynamics is embedded in social relations and social institutions. In this article, the determinants of dynamic capabilities of small manufacturing Finnish firms will be explored. Specifically we focus on the importance of social capital for firm dynamics. According to analysis, the most important antecedents of dynamic capabilities of firms are its strategy and social capital. Social capital as wide and active participation in network cooperation correlates statistically significantly with the firm dynamics. Social capital increases firm dynamics by enhancing communication and knowledge spillovers in corporate networks. Active networkers gain important information from their bridging and linking ties, such as other firms and public institutions. According to the analysis, the increase of trust in business relations does not correlate with the dynamic capabilities. Instead trust acts as a trigger factor when firms consider their network activities.
Keywords: 330; social capital; networks; trust; dynamic capabilities; small and medium sized enterprises